Odontogenic Cutaneous Fistula: A Cause of Persistent Cervical Discharge - Nicholas Figaro; Solaiman Juman (Case Reports in Medicine)
Odontogenic cutaneous fistulas often lead to intense levels of patient discomfort and suffering. Due to its rarity and the absence of dental symptoms, a considerable number of patients are usually misdiagnosed which results in inappropriate management. This case report presents a 16-year-old patient with a 2-year history of a nonhealing, persistently discharging lesion in the left submandibular region of the neck. The patient underwent exploration of the left submandibular region, and a fistulous tract directed superomedially to the ipsilateral lower molar teeth was excised. A subsequent panoramic orthopantomogram performed one week postoperatively demonstrated radiolucency is the distal root of tooth 37. A final diagnosis of odontogenic cutaneous fistula was made, and the patient was referred to the Maxillofacial Department for treatment of the offending tooth.